Perspektif Sosiologi Hukum Islam Terhadap Peran Ganda Ibu Single Parent Sebagai Pencari Nafkah Utama Dalam Keluarga: Studi Kasus Di Desa Pliwetan Kecamatan Palang Kabupaten Tuban - Trianita Sweeta Hanny Marenda; Muhammad (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This thesis aims to determine the Perspective of Islamic Legal Sociology and Structural Functionalism Theory on the dual role of single parent mothers, the views of society and the responses of single parent mothers regarding the problems and challenges faced in their households and how the views of Structural Functionalism theory on the dual role of single parent mothers. This research is a descriptive qualitative research using field or empirical studies using a sociological approach, the author in collecting data uses three data collection techniques, namely interviews, observation and documentation, while in the analysis used are reduction techniques, exposure and drawing conclusions. The conclusion of the study in general is that the phenomenon that occurs in Pliwetan Village as a mother who holds the status of a single parent or single mother can also continue to play the role of the main breadwinner in their family and also become a functional person towards her family and the surrounding community. However, this is contrary to Islamic Law where the role of the obligation to earn a living and as head of the family should be the responsibility of a husband, but in reality these roles and obligations are choices and demands for mothers who hold the status of a single parent mother.